Problems and Prospects of the Street Vendors-An Analytical Study of Dhangadi City in Nepal - Ojha, Rabin; Pant, Sumit (Brixton Scholarly Review, 2025)
Street vending is a widespread and vital profession found in nearly every country and major city worldwide. They are people selling items from a temporary structure; street vendors play a crucial role in economic activities by providing essential services and goods. This research focuses on street vendors in Dhangadhi, exploring their current status, financial problems, governance and policy issues, and working conditions. Street vending requires minimal capital and offers flexibility, making it an accessible livelihood for those unable to secure formal employment. Despite their significant contributions, street vendors often face hostility from local authorities, who sometimes attempt to remove them. This research aims to address these challenges by examining the conditions and problems faced by street vendors in Dhangadhi. Using a descriptive methodology that combines quantitative and qualitative approaches, the study collected data from 84 street vendors in four key areas of Dhangadhi: Hasanpur, Chauraha, MilanChowk, and the Buspark area. The research methodology includes a structured questionnaire refined through a pilot test based on the primary data, complemented by secondary sources. The data were analyzed using statistical techniques and presented through visual aids. This study provides valuable insights into the street vending sector in Dhangadhi, highlighting its importance to the economy and offering guidance for local authorities to develop informed policies. Addressing the financial, governance, and working conditions issues faced by street vendors can enhance their contributions to the economy.